Serum Biochemical And Enzymatic Studies During Different Stages Of Pregnancy In Cows - Harichandan, P.P.; Mohanty, D.N.; Mohanty, D.N.; Das, S.; Patra, B.K. (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
Serum biochemical and enzymatic profile of 20 cows in three different stages of pregnancy and non-pregnancy (control) was studied. The serum glucose values (mg/dl) obtained for the first, second and third trimester of pregnancy and in non-pregnant animals evinced a significant difference (p
Keywords: Cow. Serum Biochemical Constituents; Enzymatic Profile; Gestation Period